Oil palm production mechanization in Malaysia. - Bardaie, Mohd. Zohadie (1987)
Malaysia is currently the worlds leading producer of palm oil, accounting for approximately 55 per cent of world palm oil production in 1984. In that year, Malaysia produces 3.7 million tonnes of palm oil. The total area planted with oil palm throughout the country in 1984 is about 1.4 million hectares. One major problem currently faced by the palm oil industry is the unavailability of adequate labor supply for the handling of heavy and strenuous tasks such as the harvesting of fresh fruit bunches on oil palm plantations. This problem is caused mainly by the migration of labor to urban areas. This labor shortage has caused the plantation sector to lose a substantial amout of income. Most of these labor shortage problems can be alleviated by increasing the productivity of labor through mechanization. This paper discusses the current situation with regards to mechanization in the oil palm plantations. Some of the current research activities at the Department are high-lighted.